Investigating the role of conflict management strategy on development of cooperative management - Hosseinali Aziziha; Ali Khodsetan; Mahsan Hajirasouliha; Ashkan Faraji; Milad Isakhani Zakaria; Seyed Shahab Mousavi (Management Science Letters)
This paper presents an empirical study to investigate the effect of conflict management strategies on development of cooperative culture in one of Iranian auto industries. The proposed study adopts a Putnam and Wilson’s questionnaire (1982) [Putnam, L. L., & Wilson, C. E. (1982). Communication strategies in organizational conflicts: Reliability and validity of a measurement scale. Communication Yearbook, 6, 629-652.] for measuring different components of conflict management. In addition, the study also designs a questionnaire for measuring cooperative culture. Cronbach alphas are calculated for conflict management and cooperative cultures as 0.76 and 0.79, respectively. Using Spearman correlation ratio as well as regression technique, the study has determined that three components of conflict management strategies including cooperation, competition and compromise could significantly contribute of development of cooperative culture.